A protocol proposal on calculation of the metabolic rate for surgeons in an operating room - Nelson Rodrigues (2016)
Thermal comfort is a subject of great importance for the well-being and productivity of people in general, thus, a good work environment is something that should be sought whenever possible. Within this subject, the determination of the metabolic rate has great importance, although its calculation can be a laborious task. In this work, a protocol is presented to calculate the metabolic rate of a surgeon when performing his work in an operating room. The clothing, environmental conditions as well as the different tasks of the surgeon were collected through observation of three surgeries in a Portuguese hospital. These conditions were then recreated on a controlled environment of a climatic chamber and a set of tasks to reproduce the physical workload performed by the surgeon. In this controlled environment, the metabolic rate was measured using oxygen measurement and the results were compared with ISO 8996: 2004 standard values. The obtained results showed a good approach to this standard.